Short‐term echocardiographic evaluation by global longitudinal strain in patients with heart failure treated with sacubitril/valsartan. (31st March 2020) - Mazzetti, Simone; Scifo, Chiara; Abete, Raffaele; Margonato, Davide; Chioffi, Margherita; Rossi, Jessica; Pisani, Matteo; Passafaro, Giovanni; Grillo, Massimiliano; Poggio, Daniele; Mortara, Andrea
Abstract: Aims: The angiotensin receptor neprilysin inhibitor (ARNI) sacubitril/valsartan reduces mortality and hospitalizations in patients with heart failure and reduced ejection fraction (HFrEF). Favourable effects on haemodynamic and functional parameters have been observed in patients with HFrEF undergoing ARNI therapy, using standard transthoracic echocardiography. Global longitudinal strain (GLS) assessment uses a semi‐automatic procedure to provide a reliable and repeatable method that improves the detection of early changes of contractile function. We aimed to assess the effects of ARNI on GLS and myocardial mechanics in patients with HFrEF. Methods and results: Thirty patients with New York Heart Association class II–III HFrEF were treated with ARNI and monitored using standard echocardiographic examination and GLS measurements at baseline, 3 months, and 6 months. ARNI therapy resulted in a significant reduction of ventricular volumes and a significant increase in left ventricular ejection fraction at 6 months but not 3 months by standard transthoracic echocardiography (left ventricular ejection fraction from 28 ± 8% at baseline to 34 ± 12% at 6 months, P < 0.001). Non‐significant differences in the size of the left atrium, right ventricular function, and pulmonary pressures were found at 6 months. By using GLS, there was a progressive improvement of all strain parameters by 3 months. The improvement showed a progressive trend over time and maintained significance at 6 months: GLS 4ch −7.2 ± 4.8% at baseline vs. −7.5 ± 3.9% at 3 months ( P = 0.025) and − 9.2 ± 5.2% at 6 months ( P = 0.0001); AVG GLS −6.9 ± 4.3 at baseline vs. −7.9 ± 4.2 at 3 months ( P = 0.04) and − 8.8 ± 4.4 at 6 months ( P = 0.035); GLS endo 8.2 ± 4.8 at baseline vs. −9.0 ± 4.8 at 3 months ( P = 0.05) and − 10.1 ± 5.1 at 6 months ( P = 0.001). Conclusions: Sacubitril/valsartan induces an early benefit on left ventricular remodelling, which is captured by myocardial strain and not by standard echocardiography. Strain method represents a practical tool to assess early and minimal variations of left ventricular systolic function.